2010
DOI: 10.2319/121608-639.1
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of In Vivo Tooth Volume Determinations From Cone-Beam Computed Tomography

Abstract: In vivo determination of tooth volumes from CBCT data is feasible. The measurements slightly deviate from the physical volumes within -4% to 7%. Smoothing operations reduce volume measurements. Currently, no requirements for accuracy of volumetric determinations of tooth volume have been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 20 publications
4
109
0
3
Order By: Relevance
“…The presented data confirm the accuracy of volumetric measurements from CBCT data compared with mCT data. Liu et al (17) reported a slight deviation of segmented teeth volumes from the physical volumes within À4% to 7% using manual segmentation strategies and without any smoothing operations. Furthermore, Michetti et al (19) reported slightly smaller segmented root canal volumes from CBCT data (less than 3%) compared with the volumes measured from digitized images from histologic sections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presented data confirm the accuracy of volumetric measurements from CBCT data compared with mCT data. Liu et al (17) reported a slight deviation of segmented teeth volumes from the physical volumes within À4% to 7% using manual segmentation strategies and without any smoothing operations. Furthermore, Michetti et al (19) reported slightly smaller segmented root canal volumes from CBCT data (less than 3%) compared with the volumes measured from digitized images from histologic sections.…”
Section: Discussionmentioning
confidence: 99%
“…Using the livewire boundary technique, boundaries are extracted in one fifth of the time required for manual tracing but with 4.4 times greater accuracy and 4.8 times greater reproducibility (22). This proved to be of great value, especially for teeth in the posterior area of the mandible where segmentation is more difficult because of the cortical bone (17). Furthermore, using 3D semiautomatic active contour level set methods available in ITK-SNAP offers the advantages of a greatly reduced working time, high accuracy, and real-time interaction with the segmentation process in contrast to the commonly used low-level methods (region growing).…”
Section: Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…18 When segmentation of an object is performed with different thresholds, the threshold values must be changed. 19 For example, since the bone density is low and multiple bones overlap in the mandibular head region, segmentation is more difficult than in other regions. 20 In this study, the mandible was displayed in the Analyze ROI window, and the thresholds for the area within the perimeter of the mandibular cortex were defined on all slides.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are quantitative studies carried out on the use of CBCT systems and software in dental volumetric analysis [4,[10][11][12][13][14][15][16][17]; however, the effect of section thickness on the accuracy of the volume estimate obtained by using CBCT has not been researched in these studies.…”
Section: Introductionmentioning
confidence: 99%